The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1159/000336762
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Association of White Matter Lesions with Ipsilateral Carotid Artery Stenosis

Abstract: Background: White matter lesions (WML) are commonly seen on brain MRI and are generally considered a marker of tissue damage from cerebral small vessel disease. WML are associated with increasing age and vascular risk factors, but their precise cause is unknown. A role for carotid artery atherothromboemboli has been suggested. If this is the case, more WML would be expected ipsilateral to increasing degrees of carotid stenosis. Methods: We recruited patients with ischaemic stroke from two large, separate prosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
2
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 56 publications
4
44
2
1
Order By: Relevance
“…First, in the casecase comparison within the OXVASC Study, we did not find any independent association between WMC and unilateral or bilateral carotid stenosis (≥50%) or atrial fibrillation (Table 2). Second, previous studies have also shown that there seems to be no association between WMC and side or severity of atherosclerotic carotid stenosis 39 or atrial fibrillation. 34 WMC are clearly related strongly to age, irrespective of any major role of vascular risk factors.…”
Section: Discussionmentioning
confidence: 93%
“…First, in the casecase comparison within the OXVASC Study, we did not find any independent association between WMC and unilateral or bilateral carotid stenosis (≥50%) or atrial fibrillation (Table 2). Second, previous studies have also shown that there seems to be no association between WMC and side or severity of atherosclerotic carotid stenosis 39 or atrial fibrillation. 34 WMC are clearly related strongly to age, irrespective of any major role of vascular risk factors.…”
Section: Discussionmentioning
confidence: 93%
“…64 Although the bilateral common carotid artery stenosis model cannot replicate small vessel vasculopathy or lacunar infarcts or model SVD, it possesses advantages in terms of reproducibility of WM pathology, characterized by BBB disruption, glial activation, oxidative stress, and oligodendrocyte loss. [65][66][67][68][69] Although clinically there is no direct evidence of an association between carotid stenosis and SVD or cognitive decline, once confounding risk factors are corrected for, 13,70,71 altered hemodynamics following bilateral common carotid artery stenosis results in opening of the endothelial tight junction only 2 hours after manipulation, which can be suppressed by matrix metalloproteinase 2 (MMP2) inhibitors. 66,68 MMP2, an extracellular matrix degradation enzyme, is also known to degrade the tight junction proteins ZO-1, claudin-5, and occludin, as well as induce BBB breakdown.…”
Section: Large and Small Artery Cross Talk: Role Of Altered Hemodynammentioning
confidence: 99%
“…Несмотря на то что модель двустороннего стеноза общей сонной артерии не позволяет воспроизвести васкулопатию мелких сосудов, лакунарные инфаркты или поражения, характерные для БМЦС, она обладает преимуществами с точки зрения воспроизводимости патологии БВГМ, характеризующей-ся нарушением ГЭБ, активацией глии, оксидантным стрессом и гибелью олигодендроцитов [65][66][67][68][69]. Несмотря на отсутствие прямых клинических доказательств связи стеноза и БМЦС или развития когнитивных нарушений, при внесении поправок на вмешивающиеся факторы [13,70,71] нарушение гемодинамики в результате двусто-роннего стеноза приводит к открытию эндотелиальных плотных контактов только через 2 часа после манипуля-ций, которое можно подавить с помощью ингибиторов матричной металлопротеиназы-2 (MMP2) [66,68]. Также известно, что MMP2, фермент деградации внеклеточного матрикса, также разрушает белки плотных контактов ZO-1, клаудин-5 и окклюдин и индуцирует разрушение ГЭБ [72].…”
Section: патологический каскад бмцс: роль артериальной гипертензии и unclassified
“…Although there is no association between carotid stenosis and SVD in humans, 25 small vessel changes have been linked to histologic features that have been interpreted as representing local hypoperfusion of as yet unknown cause. 26 We therefore hypothesized that sustained hypoperfusion would produce progressive pathologic and cognitive features similar to those seen in SVD.…”
Section: Introductionmentioning
confidence: 99%